Aktifitas Pelarut Fosfat Isolat Aktinomisetes asal Tanah Rizosfer Hutan Pinus Malino, Sulawesi Selatan - Sari, Sitti Rahmah (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
Actinomycetes is a gram-positive bacterium with high GC (Guanine-Cyto sine) content that has the potential as a biohygiene agent, one of which is to free bound phosphate in the soil so that it can be absorbed by plants. Phosphate contained in soil that can be utilized by plants directly is only available in limited quantities because most of the others are bound by other compounds. In this study, 15 actinomycetes isolates from the rhizosphere soil of Malino pine forest in South Sulawesi were tested for their ability to dissolve phosphate. The method used to test the phosphate solubilizing activity was by growing the isolates on pikovskaya media. Six of the 15 isolates showed phosphate solubilization activity with the highest phosphate solubility index (IKF), namely isolate RWM 5. This indicates that actinomycetes have the ability as biological control agents that secrete enzymes to release bound phosphate into phosphate that can be utilized by plants.